THE PECULIARITIES OF UZBEK AND AMERICAN CUSTOMS AND TRADITIONS - Ibragimova Dilafruz Shukhratovna; Sobirjonova Gulhayo Dilmurod qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Every culture in the world has its own unique customs and traditions that shape its identity and way of life. Uzbekistan and the United States are no exceptions. These two countries, situated on opposite sides of the globe, have distinct customs and traditions that reflect their histories, values, and cultural influences. This article depicts the peculiarities of Uzbek and American customs and traditions.